Hepatopleural Fistula with Empyema Thoracis: A Rare Complication of Autosomal Dominant Polycystic Kidney Disease. Issue 1 (2018) - Maytapa, Jeerawat; Thanapirom, Kessarin; Treeprasertsuk, Sombat; Komolmit, Piyawat; Chaopathomkul, Bundit; Kullavanijaya, Pinit
ABSTRACT : N/A: We report a 70‐year‐old man with autosomal dominant polycystic kidney disease (ADPKD) who presented with right‐sided extended‐spectrum beta‐lactamases Escherichia coli empyema thoracis. Chest and abdominal computed tomography showed hepatopleural fistula. The patient refused a surgical operation and was treated with tube thoracotomy, percutaneous drainage of dominant liver cyst, and intravenous antibiotics. His symptoms improved after 2 months of nonsurgical treatment.